Intervensi Apoteker Dalam Edukasi dan Pengelolaan Pada Obesitas Sebagai Faktor Risiko Diabetes Mellitus Tipe 2: Tinjauan Literatur - Simorangkir, Rahel Lambok Yohana; Karmawan, Zalfa Nadia Prasasti; Kalalo, Jef Gishard Kristo (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Obesity is one of the major modifiable risk factors contributing to the rising prevalence of type 2 diabetes mellitus (T2DM). Pharmacists play an essential role in health promotion and preventive care through patient education and lifestyle counseling. This review aims to summarize and critically evaluate pharmacist-led interventions in obesity management as an effort to prevent T2DM. Literature searches were conducted using Google Scholar and PubMed with the keywords “pharmacist,” “obesity,” “type 2 diabetes,” and “lifestyle modification.” From the search results, ten international intervention studies published within the last ten years met the inclusion criteria and were analyzed in detail. Findings indicate that pharmacist interventions, such as structured education, medication optimization, motivational counseling, and clinical monitoring, significantly improved weight reduction, body mass index, HbA1c levels, and adherence to healthy behaviors. Pharmacists also play a key role in deprescribing, monitoring metabolic outcomes, and supporting patient self-management. Overall, pharmacist involvement in obesity prevention and T2DM control demonstrates measurable clinical benefits and has strong potential to be adapted into national healthcare systems.